An extension of the cayley?hamilton theorem for nonlinear time-varying systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The classical Cayley-Hamilton theorem is extended to nonlinear time-varying systems with square and rectangular systemmatrices. It is shown that in both cases system matrices satisfy many equations with coefficients being the coefficients ofcharacteristic polynomials of suitable square matrices. The proposed theorems are illustrated with numerical examples.
Keywords: extension; Cayley-Hamilton theorem; nonlinear analysis; time-varying system